2021
DOI: 10.3390/agriculture11060487
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impacts of Extreme Precipitation Change on Vegetation Activity

Abstract: Extreme climate events frequently have more severe effects on terrestrial vegetation activity than long-term changes in climate averages. However, changes in extreme climate events as well as their potential risk on vegetation activity are still poorly understood. By using the Middle and Lower Reaches of the Yangtze River (MLR-YR) in China as an example, this paper aims to understand the vegetation response to changes in extreme precipitation events from 1982 to 2012 using the maximum normalized difference veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
(73 reference statements)
0
2
1
Order By: Relevance
“…Moreover, Tan (2015), Cui (2019), and Felton (2019) found a significant correlation between NDVI and extreme rainfall [38][39][40]. Pei (2021) and Zhao (2018) concluded that increased intensity and frequency of extreme precipitation promoted vegetation growth [11,41]. In the present study, NDVI is significantly and positively correlated with extreme precipitation index, a finding that differs from Zhao, Dai et al's study [6].…”
Section: Correlation Analysis Between Climatic Factors and Vegetation...contrasting
confidence: 53%
See 1 more Smart Citation
“…Moreover, Tan (2015), Cui (2019), and Felton (2019) found a significant correlation between NDVI and extreme rainfall [38][39][40]. Pei (2021) and Zhao (2018) concluded that increased intensity and frequency of extreme precipitation promoted vegetation growth [11,41]. In the present study, NDVI is significantly and positively correlated with extreme precipitation index, a finding that differs from Zhao, Dai et al's study [6].…”
Section: Correlation Analysis Between Climatic Factors and Vegetation...contrasting
confidence: 53%
“…Over the past few decades, regional temperature and precipitation conditions in the region have changed significantly, with extreme weather events occurring frequently and regional vegetation undergoing significant changes [11,23]. Park and Sohn found a significant increasing trend of NDVI in northeast China (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) • N, 110-125 • E) during 1982-2006, a weak, increasing trend of NDVI in the area from eastern Mongolia to Manzhouli, and a decreasing trend in the area southeast of Lake Baikal [24]. Zhou, Zhao et al found a significant increase in NDVI during the growing season in southeastern Horqin, China, and a significant decrease in NDVI during the growing season in Hunshandak during 1982-2011 [25].…”
Section: Introductionmentioning
confidence: 99%
“…2. To capture extremes which have an impact on society and infrastructure; for example, extreme indices like TXge35, TR, and SU have the largest impacts on health [49], whereas indices like Rx1day, CDD, and CWD have the largest impact on agriculture, water resources and the economy [50,51].…”
Section: Cmip6 Gcmsmentioning
confidence: 99%